How the ongoing armed conflict between Russia and Ukraine can affect the global wheat food security? - Mottaleb, Khondoker Abdul; Govindan, Velu (Frontiers in Food Science and Technology, 2023)
Introduction: This study examines the potential impacts of Russia-Ukraine armed conflict on the consumption and trade of wheat and wheat food security. Russia and Ukraine jointly supply more than one-fourth of total wheat in the international market. Because of the ongoing armed conflict between Russia and Ukraine, wheat export from these two countries is heavily disrupted. Applying an ex-ante impact assessment procedure, this study examines the potential impacts of Russia-Ukraine armed conflict on the consumption and trade of wheat and wheat food security. Methods: This study considered 115 countries and grouped them based on their geographic location. The sampled countries are grouped as: South Asia, Sub-Saharan Africa, Southeast Asia, Central Asia, North Africa, Middle East, and rest of the world. Simulation results are presented by the geographic location of the sampled countries. To assess the potential impacts of the ongoing Ukraine-Russia armed conflict on wheat food security in the sampled countries, this study mainly sourced data from FAOSTAT. This study first calculates the share of wheat consumption imported from Russia and Ukraine. Then, this study calculates the daily total calorie and protein intake exclusively from the imported wheat from Russia and Ukraine in the sampled countries by their groups. It is found that 1 kg of wheat provides roughly 2,839–2,965 kilocalories (kcal) of energy, and between 81 and 88 g (gm) of protein, in the sampled countries. Using the conversion factors, this study assesses the impacts of a reduction of wheat exports in the global market due to the ongoing armed conflict between Russia and Ukraine applying an ex-ante assessment process. Specifically, this study assumes a 100% and 50% reduction in wheat exports by Russia and Ukraine, and then estimates its impact on daily calorie and protein intake in the sampled countries. Results: The ex-ante simulation shows that, under the assumption of a 100% reduction of wheat exports from Russia and Ukraine and assuming alternative wheat import sources are unavailable, yearly per capita wheat consumption would be reduced by 19% in South Asia, 57% in Sub-Saharan Africa, 26% in Southeast Asia, nearly 39% in Central Asia, the Middle East and North Africa, and 27% in other areas. Consequently, daily per capita calorie intake in South Asia would fall by more than 3%, in Sub-Saharan Africa by more than 6%, in Southeast Asia by 2.2%, in Central Asia, the Middle East, and North Africa by 14%, and in the other countries of our study by 6.2%. A 50% reduction of wheat exports by Russia and Ukraine without substitute supplies of wheat grain would also substantially reduce wheat consumption as well as daily calorie and protein intakes from wheat, in the sampled countries. Discussions: Malnutrition and hunger are widespread in many countries of Asia and Africa that depend on wheat and other imported cereals to meet their rising food demand. Rising wheat prices, particularly in countries that rely on imported wheat, can lead to violence and social unrest, as occurred during 2007-11. Based on the findings, to avoid hunger and supply shock related disaster in the future, this study urges to search alternative sources of wheat for the import-dependent, resource-poor countries. Eventually, as there are few alternatives to increase wheat supply other than enhancing yield gain, this study strongly suggests for steady public funding for adaptive and basic research to harness genetic gains for yield and climatic adaptation in wheat. Also, in the long run, it is necessary to explore the possibility of wheat area expansion in the suitable countries. For example, a recent study confirmed the potentiality of wheat area expansion in Argentina and Brazil. Also, there is also a possibility of expansion of wheat area in Sub-Saharan African countries. Exploring opportunities for the expansion and sustainable intensification of wheat production in suitable countries can be instrumental to ensuring self-sufficiency in wheat supplies in Sub-Saharan Africa.